GIS-basierte multidimensionale Verfahren zur optimalen Baulandentwicklung im Städtebau – anhand des Beispiels des innerstädtischen Projekts Holsten-Areal in Hamburg - Naumann, Lion Lukas; Nadler, Michael (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
The global urban growth trend is also evident in Germany and the pressure on the real estate markets is pushing construction activity to the threshold of available building land. To limit urban expansion, additional space is to be created primarily through brownfield development, but here large housing potentials are usually only to be found on sites that are difficult to develop. The framework conditions that have arisen here in the interplay between land and real estatemarkets in conjunctionwith the multidimensionality of urban planning problems suggest a need for urban planners and researchers to develop more effectivemethods. This paper therefore describes a GISbasedmethod for optimising building sites, which can be used to evaluate sites in context and optimise them attribute-spatially. It combines a fuzzy methodology with a heuristic optimisation algorithm, the Parameterised Region-Growing, and demonstrates it using the example of the Holsten site in Hamburg. It successfully generates spatially compact and coherent, highly valued residential building areas, to which urban development parameters are assigned. Comparisons with existing planning show instructive results, e.g., regarding more effective utilisation of good micro-locations, realistic buildingdensity values and realisable area parameters.
Keywords: Suitability assessment; Land-use optimization; Fuzzy suitability modelling; Parameterized region-growing; Decision support